Selective rearrangement of terminal epoxides into methylketones catalysed by a nucleophilic rhodium-NHC-pincer complex - Jürgens, Eva; Rominger, Frank (Chemical communications, 2015)
An efficient RhI-NHC-pincer catalyst for the highly regioselective Meinwald rearrangement of monoalkylated epoxides into methylketones under mild conditions is presented. The nucleophilic epoxide opening is assisted by Lewis acids.
First published 22 Dec 2014
Gesehen am 17.06.2020